Hydrophilic Divinylbenzene for Equilibrium Sorption of Emerging Organic Contaminants in Aquatic Matrices - Huysman, Steve; Vanryckeghem, Francis; De Paepe, Ellen; Smedes, Foppe; Haughey, Simon A; Elliott, Christopher T; Demeestere, Kristof; Vanhaecke, Lynn (Environmental science & technology, 2019)
Hydrophilic divinylbenzene (DVB) (Bakerbond) has surfaced as a promising sorbent for active sampling of analytes from aqueous matrices over a very broad polarity range. Given this, hydrophilic DVB may likewise offer potential for passive sampling, if sorbent/water partitioning coefficients (Ksw) were to be available. In this work, static exposure batch experiments were performed to quantitatively study the equilibrium sorption of 131 environmentally relevant organic contaminants (P values ranging from -1.30 to 9.85) on hydrophilic DVB. The superior affinity of hydrophilic DVB, as compared to Oasis HLB, for compounds with a broad polarity range was confirmed by functional Fourier-transform infrared spectroscopy and Raman characterization, demonstrating the presence of carboxyl moieties. Concentration effects were studied by increasing compound concentrations in mixture experiments and resulted in the steroidal endocrine disrupting compounds in higher Ksw, while lower Ksw were obtained for the (alkyl)phenols, personal care products, pesticides, pharmaceuticals, and phthalates. Nevertheless, Ksw remained constant in the said design for equilibrium water concentrations at environmentally relevant seawater levels. An independent analysis of thermodynamic parameters (change in enthalpy, entropy, and Gibbs free energy) revealed the nature of the main partitioning processes. While polar (log P < 4) compounds were mainly served by physisorption, nonpolar (log P > 4) compounds also exhibited binding by multiple hydrogen bonding. In conclusion, this research facilitates the future application of hydrophilic DVB for active as well as passive sampling in the analysis of organic contaminants for monitoring purposes and for toxicity testing.
Keywords: Water Pollutants, Chemical; vinylové sloučeniny; Pesticides; pesticidy; Vinyl Compounds; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions; chemické látky znečišťující vodu